2011
DOI: 10.2174/1874325001105010037
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Single-Arm, Multi-Center Trial of a Patient-Specific Interpositional Knee Implant: Early Clinical Results

Abstract: Background:The treatment of unicompartmental arthritis in younger patients is challenging. The aim of this study is to report final safety and efficacy analysis results for the iForma patient–specific interpositional device, which is designed for the treatment of isolated medial or lateral compartment arthritis of the knee.Methods:From June 2005 to June 2008 78 subjects (42 men, 36 women) received an iForma implant. The mean age was 53 years, the mean Body Mass Index 29.0. We surveyed the WOMAC scores, the vis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The main anticipated complications of such device include implant dislocation, and increased fatigue or wear if the implant is pressed into a location/ orientation in which it is not congruent with the other surfaces. Dislocation has been reported frequently for metal interpositional spacers, and it seems to be one of the main reason they are no longer available for commercial use (Bailie et al, 2007;Koeck et al, 2011). While the exact passive motion patterns of the PCU implant were not quantified in the current study, preliminary clinical data suggests that the implant moves between approximately 10 mm anteriorly and 7 mm posteriorly in-vivo, with some rotation (de Coninck et al, 2014).…”
Section: Discussionmentioning
confidence: 72%
“…The main anticipated complications of such device include implant dislocation, and increased fatigue or wear if the implant is pressed into a location/ orientation in which it is not congruent with the other surfaces. Dislocation has been reported frequently for metal interpositional spacers, and it seems to be one of the main reason they are no longer available for commercial use (Bailie et al, 2007;Koeck et al, 2011). While the exact passive motion patterns of the PCU implant were not quantified in the current study, preliminary clinical data suggests that the implant moves between approximately 10 mm anteriorly and 7 mm posteriorly in-vivo, with some rotation (de Coninck et al, 2014).…”
Section: Discussionmentioning
confidence: 72%
“…Felts [12] and Parratte [19] demonstrated that polyethylene wear remains a major problem affecting the survival of UKR in younger active population. Recently, for those patients who have passed the age for biological cartilage repair, but are considered too young for traditional, more invasive joint replacement, modern patient‐specific interpositional devices may be a good solution [15].…”
Section: Discussionmentioning
confidence: 99%
“…The electronic search returned 2766 articles, of which 390 were duplicates and 2346 excluded after reading their titles and abstracts. Of the remaining 30 articles, 13 were not relevant [6, 11, 17, 19, 21, 23, 26, 28, 29, 37, 39, 40, 43], one was a review [41], and one an in‐vitro study [44], which were all excluded after reading their full texts. This left 15 articles that were eligible for data extraction, of which six were on custom UKA [2, 13, 16, 22, 27, 45], six on custom BKA [3, 7, 33, 36, 42, 49], and three on custom PFA [9, 12, 38] (Fig.…”
Section: Resultsmentioning
confidence: 99%